'It's like taking a bit of masculinity away from you': towards a theoretical understanding of men's experiences of infertility. Issue 6 (8th March 2017) - Dolan, Alan; Lomas, Tim; Ghobara, Tarek; Hartshorne, Geraldine
Abstract: In the UK, nearly half of all cases of infertility involve a 'male‐factor'. Yet, little empirical work has explored how men as men negotiate this terrain. Three interrelated concepts; 'hegemonic masculinity', 'embodied masculinity' and the linkages between 'masculinities' and male help‐seeking, provide the theoretical framework that guided a qualitative study conducted with 22 men experiencing infertility. The paper explores men's propensity to delay their help‐seeking in relation to infertility despite their desire for children. It also demonstrates how, in the context of infertility, the male body can be defined as both a failed entity in itself (unable to father a child) and a subordinated social entity (unable to measure up to hegemonic ideals) that characterises men's masculine identities. The paper also illustrates how men appear willing to accept responsibility for their infertility and adopt aspects of hitherto subordinate masculine practice. This does not, however, constitute the total unravelling of well understood and accepted expressions of masculinity. Finally, the paper demonstrates how infertility is perceived as having the potential to fracture current and even future relationships. Moreover, regardless of how well men measured up to other hegemonic ideals, ultimately they can do little to counteract the threat of other (fertile) men.